Immunotropic effects of vitamin D3 in original rectal suppositories in experimental ulcerative colitis - M. V. Osikov; M. S. Boyko; E. V. Simonyan; V. A. Ushakova (Медицинская иммунология, 2021)
Increased incidence of ulcerative colitis (UC) is a prerequisite for searching new therapeutic approaches, primarily with an opportunity of site-directed impact on the colon lesion. UC pathogenesis is associated with dysregulated immune response, and limited effectiveness of basic therapy for the disorder. Vitamin D3 exhibits antioxidant, anti-inflammatory, immunomodulatory and other properties, it has been shown to be effective in some autoimmune diseases, thus prompting us to study its effect on immune status in UC. We aimed for studying the effect of vitamin D3, as a component of original rectal suppositories, upon clinical course and indexes of immune status in experimental UC. UC in rats was modeled with 3% oxazolone solution. The vitamin D3-containing suppositories (1500 IU) weighing 300 mg were administered per rectum every 12 hours for 6 days. On days 2, 4 and 6 of UC, the clinical features were assessed as well as blood leukocyte counts, numbers of CD3+, CD45RA+; absorbing and NBT-reducing abilities of blood neutrophils were determined; IgM, IgG, IL-6 and IL-8 concentrations in serum were also studied.The DAI index increased in non-treated UC, along with raised neutrophil numbers in blood, their absorption and NBT-reducing activity was also increased, the total number of lymphocytes, including CD3+, CD45RA+ became higher, serum concentrations of IgM, IgG, IL-6, IL-8 increased. Local use of vitamin D3 in UC reduces DAI parameters, causes decrease in blood neutrophil counts, reducing and partially restoring absorptive and NBT-reducing abilities of neutrophils, decline of total lymphocyte counts in blood, partially restoring the CD3+ and CD45RA+ numbers, causing decline and partial restoration of serum IgM, IgG, IL-6, IL-8 concentrations. An association between clinical signs and indexes of immune status in UC was established under the conditions of vitamin D3 use. Conclusions: The protective effect of vitamin D3 in UC can be mediated by its antioxidant effect, changes in production of immunoregulatory cytokines, modulation of Th1-, Th2-, Th17-dependent reactions and Treg activity, being a pre-requisite for further studies to clarify the mechanism of vitamin D3 immunotropic action in UC,with an opportunity of using it in clinical practice.